2023
DOI: 10.1161/atvbaha.123.319816
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelial Cell APOE3 Regulates Neurovascular, Neuronal, and Behavioral Function

Felecia M. Marottoli,
Hui Zhang,
Eden Flores-Barrera
et al.

Abstract: BACKGROUND: Specialized brain endothelial cells and human APOE3 are independently important for neurovascular function, yet whether APOE3 expression by endothelial cells contributes to brain function is currently unknown. In the present study, we determined whether the loss of endothelial cell APOE3 impacts brain vascular and neural function. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…ApoE3 has been shown to inhibit Rho activation, reducing the formation of actin stress bers and focal adhesions and leading to cellular softening 46 . Speci c knock-out ApoE3 gene in endothelia causes neurovascular dysfunction and increase permeability in the mice 47 . Using ApoE-/mice, it has been demonstrated that the main proteins modulated by hyperlipidemic stress are involved in actin-dependent pathways 48 .…”
Section: Discussionmentioning
confidence: 99%
“…ApoE3 has been shown to inhibit Rho activation, reducing the formation of actin stress bers and focal adhesions and leading to cellular softening 46 . Speci c knock-out ApoE3 gene in endothelia causes neurovascular dysfunction and increase permeability in the mice 47 . Using ApoE-/mice, it has been demonstrated that the main proteins modulated by hyperlipidemic stress are involved in actin-dependent pathways 48 .…”
Section: Discussionmentioning
confidence: 99%